Technology education gender V. Sukhomlinsky (Pedagogy of Higher and Secondary Education, 2013)
Butenko O. H. Technology education gender V. Sukhomlinsky.The article analyzes the creative heritage of V. Sukhomlynsky that reviewed the education of the younger generation qualities of masculinity and femininity as one of the most important tasks of moral education of the individual. It is shown that universal education pavlyskoho teacher who combines original ideas and innovative technologies that sound important today, is fertile ground for gender Upbringing.
Keywords: gender; gender education